Scientific and applied components of assessing the impact of measures on the implementation of the selected innovative strategy on the economic productivity of the operating system of a construction enterprise - Malykhina, O.M.; Ananko, E.I.; Movseyan, A.S.; Sargsyan, V.G.; Vovkovich, Y.V. (Ways to Improve Construction Efficiency, 2023)
The scientific and practical elements of such an assessment are based on a systematic approach to the analysis of the implementation of innovative technologies and processes in the construction industry. It is important to note that increasing the economic efficiency of the management system is based on the principle of comprehensive integration of innovations into all levels of the enterprise, starting from planning and design and ending with the direct implementation of construction projects. Innovative measures include process automation, implementation of project management information systems, optimization of resource use, improvement of logistics and other business processes. An important aspect of assessing the impact of innovations is determining the performance indicators of the business system that will be improved due to the implementation of innovations. Economic efficiency can be measured both at the level of individual processes and at the level of the enterprise as a whole. Key indicators are labor productivity, speed of construction work, cost optimization, reduction of project implementation times and improvement of the quality of building materials and structures. It is also important to take into account the stability of the enterprise system to external factors, such as economic fluctuations, changes in legislation, natural and climatic conditions. Evaluation of innovation strategies from a scientific and applied point of view requires a multidimensional analysis of the risks and opportunities that arise when implementing innovations. Since the innovation process is always associated with a certain degree of uncertainty, it is important to use analytical methods to predict the consequences of the introduction of new technologies. Such methods include econometric modeling, scenario analysis, statistical data analysis, and the use of decision support systems based on artificial intelligence. The implementation of innovation strategies involves not only technological changes, but also organizational changes in construction companies. Clear change management and flexible adaptation to new situations are important for increasing the economic efficiency of operating systems. It is important to train personnel to adapt to new technologies, create a new management culture aimed at supporting innovations, and develop new mechanisms for motivating employees.